Inventarisasi Jenis Tumbuhan Obat Di Hutan Mangrove Desa Margasari Kecamatan Labuhan Maringgai Lampung Timur - Supriyanto Supriyanto; Indriyanto Indriyanto; Afif Bintoro (Department of Forestry, Faculty of Agriculture, University of Lampung, 2014)
Mangrove forest in Lampung Mangrove Center (LMC) Margasari village at East Lampung is one area that still has good condition to keep a variety of potential to be explored such as medicinal plants. Purpose of this study was to determine of species, diversity, and functional properties of mangrove plants for medicine. Research conducted in April 2012 in village 12 Translok at Margasari village East Lampung. Data retrieval is using method checkered lines, and interviews with the public, as well as literature. Number of sample plots used 12 pieces. Data were analyzed using the formula density, relative density, frequency, relative frequency, important value index, and diversity index Shannon. Based on the result of the research have been known 7 species of plants as medicine, among others: api-api (Avicennia marina) to cure rheumatism and toothache; jeruju (Acanthus ilicifolius) cure for cancer and diabetic; nipa (Nypa fruticans) medication for asthma and diabetes; bakau (Rhizophora apiculata) for antiseptic; beluntas (Pluchea indica) for body odor; jenu (Derris trifoliata) for a laxative; and tapak kuda (Ipomoea pescaprae) to cure wounds and ulcers. Api-api is a dominant plant and widest spread because it has an important index as value high as 144.24% and frequency 67.5%. Beluntas plant has the highest density of 12,708.33 individual/ha.Mangrove forest Margasari village at village 12 Translok have low diversity, because the calculation of the index obtained values Shannon H'=0.44. Keywords: inventory, mangrove forest, medicinal plant